2015
DOI: 10.1089/aid.2014.0126
|View full text |Cite
|
Sign up to set email alerts
|

Low-Density Lipoprotein Cholesterol Levels and Statin Treatment by HIV Status Among Multicenter AIDS Cohort Study Men

Abstract: Treating cardiovascular disease (CVD) risk factors, including dyslipidemia, is important in HIV care. Low-density lipoprotein cholesterol (LDL-c) target achievement is a readily available benchmark for dyslipidemia control, although use of this target is not uniformly endorsed by professional societies. We examined whether HIV serostatus is associated with not achieving LDL-c target. Among Multicenter AIDS Cohort Study (MACS) participants completing visit 56 (10/1/2011-3/31/2012), we categorized each man as on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…The period prevalence estimates obtained for the sample of adult HIV‐infected patients in the DC Cohort are generalizable to the broader HIV‐infected outpatient population in a large urban US city. Half of HIV‐infected patients in the DC Cohort were classified as hypertensive, which represents a higher prevalence compared with the 32% of participants in the EuroSIDA study , 14% of participants in the D:A:D study , 45% of participants in the Swiss HIV Cohort Study , 32% of male patients in the VACS‐VC , 32% of female patients in the WIHS , 43% of HIV‐infected outpatients at an urban New York health centre , and 44% of male patients in the MACS with hypertension , although it also represents a marginally lower prevalence compared with the 54% of male patients and 57% of female patients in the HOPS with hypertension . Among DC Cohort patients, 12% of male patients and 16% of female patients had diabetes, which was comparable to the 12% of male patients and 19% of female patients in the HOPS , 13% of male patients in the MACS , 14% of male patients in the VACS‐VC , and 18% of female patients in the WIHS with diabetes , but higher than the 5% of participants in the EuroSIDA study , 3% in the D:A:D study , and 7% in the Swiss HIV Cohort Study with diabetes .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The period prevalence estimates obtained for the sample of adult HIV‐infected patients in the DC Cohort are generalizable to the broader HIV‐infected outpatient population in a large urban US city. Half of HIV‐infected patients in the DC Cohort were classified as hypertensive, which represents a higher prevalence compared with the 32% of participants in the EuroSIDA study , 14% of participants in the D:A:D study , 45% of participants in the Swiss HIV Cohort Study , 32% of male patients in the VACS‐VC , 32% of female patients in the WIHS , 43% of HIV‐infected outpatients at an urban New York health centre , and 44% of male patients in the MACS with hypertension , although it also represents a marginally lower prevalence compared with the 54% of male patients and 57% of female patients in the HOPS with hypertension . Among DC Cohort patients, 12% of male patients and 16% of female patients had diabetes, which was comparable to the 12% of male patients and 19% of female patients in the HOPS , 13% of male patients in the MACS , 14% of male patients in the VACS‐VC , and 18% of female patients in the WIHS with diabetes , but higher than the 5% of participants in the EuroSIDA study , 3% in the D:A:D study , and 7% in the Swiss HIV Cohort Study with diabetes .…”
Section: Discussionmentioning
confidence: 92%
“…Half of HIV‐infected patients in the DC Cohort were classified as hypertensive, which represents a higher prevalence compared with the 32% of participants in the EuroSIDA study , 14% of participants in the D:A:D study , 45% of participants in the Swiss HIV Cohort Study , 32% of male patients in the VACS‐VC , 32% of female patients in the WIHS , 43% of HIV‐infected outpatients at an urban New York health centre , and 44% of male patients in the MACS with hypertension , although it also represents a marginally lower prevalence compared with the 54% of male patients and 57% of female patients in the HOPS with hypertension . Among DC Cohort patients, 12% of male patients and 16% of female patients had diabetes, which was comparable to the 12% of male patients and 19% of female patients in the HOPS , 13% of male patients in the MACS , 14% of male patients in the VACS‐VC , and 18% of female patients in the WIHS with diabetes , but higher than the 5% of participants in the EuroSIDA study , 3% in the D:A:D study , and 7% in the Swiss HIV Cohort Study with diabetes . More than half of male patients and more than 40% of female patients in the DC Cohort were classified as dyslipidaemic, and these prevalences are higher than the 37% of male patients and 31% of female patients at an urban New York health centre , 45% of EuroSIDA study participants , and 42% of D:A:D study participants with dyslipidaemia , but lower than the 58% of male patients in the VACS‐VC , 81% of male patients and 67% of female patients in the HOPS , and 92% of male patients in a MACS substudy with dyslipidaemia ; these large differences might be attributed to different histories of ARV therapy and/or the use of different quantitative cut‐offs for various lipid parameters to define dyslipidaemia.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The association of hepatitis C and statin use is important in light of our earlier study which demonstrated that chronic hepatitis C infection was associated with higher CHD risk [unpublished data]. A recent data analysis from the Multicenter AIDS Cohort Study (MACS) showed elevated transaminase levels were associated with not achieving LDL-c targets suggesting a reluctance of providers to initiate statins which are potentially hepatotoxic [33]. This may explain the underutilization of statins among HIV-hepatitis C co-infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in findings may be due to differences in patient and provider study populations [34]. In the HIV Outpatient Study (HOPS) and MACS analyses, however, current smoking was associated with lesser achievement of target LDL-c goals which may be explained by lower LDL-c targets due to presence of this risk factor that require more aggressive lipid-lowering therapy [26,33]. These observations are important because of the higher prevalence and risk of MI attributed to smoking in the HIV population compared to the general population [8].…”
Section: Discussionmentioning
confidence: 99%